Pleomorphic Adenoma of the External Auditory Canal: A Rare Presentation - Samir Jaber; Milan Rudic; Ivan James Keogh (Case Reports in Otolaryngology)
A 55-year-old male presented with a nine-month history of gradually enlarging, painless mass in the right external auditory canal associated with hearing loss and occasional bleeding. Examination demonstrated complete obstruction of the outer 1/3 of the external auditory canal by a firm, pink, rubbery mass. CT scan of the temporal bone showed tumor mass with no evidence of bone destruction. The tumor was excised and histopathology confirmed a diagnosis of ceruminous pleomorphic adenoma of the external auditory canal. Six months following the surgery, patient is free of any recurrent disease.